PENGENALAN BUDAYA JEPANG DAN PROSPEK LULUSAN BAHASA JEPANG - Aprilani, Felicia; Amalia, Aan; Nurohmah, Hety; Gayatri Ranadireksa, Dinda; Jaohari, Abdul Latif; Ulun Sundasewu, Rama (Jurnal Abdimas Bina Bangsa, 2025)
The Community Service Program (P2M) is an activity in an effort to implement one of the dharmas of   the Tridharma of Higher Education. This activity is carried out routinely and periodically by the Japanese Language Study Program and also other study programs within Widyatama University as an embodiment of the Tri Darma of Higher Education. This activity is a medium for interacting with the community as a form of concern for the Japanese Language Study Program towards the community and is not only oriented towards internal activities. Japanese, in the Middle School environment, both at Senior High Schools (SMA) and Vocational High Schools, is a cross-interest subject that is given from the beginning to the end of the education period. This is in accordance with the national curriculum issued by the Ministry of National Education. Thus, the ability to communicate in Japanese is considered important to improve the quality of graduates. High school graduates will not only receive a certificate of completion of studies but also certificates of other competencies including Japanese. The benefits of Japanese for students can be as a provision to continue their studies or additional skills to enter the world of work. In response to this, the Widyatama University Bandung Japanese Language Study Program as an institution whose aim is to develop and introduce Japanese language and culture is moved to provide knowledge of Japanese language and culture to high school/vocational school students through Community Service (PkM) activities.